Hebreos, romanos, moros e Incas: Garcilaso de la Vega y la arqueología andaluza - Carmen Bernand (Nuevo mundo - Mundos Nuevos, 2011)
This paper deals with the close relationship between Inca Garcilaso de la Vega and the Andalusian antiquaries, especially Ambrosio de Morales. Garcilaso drew his inspiration from this scholar when he spoke about the « antiguallas » (antiquities) of the Inca. Conversely the Andalusian antiquaries took from Garcilaso many ideas about the first « mestizajes » in Spain. The Bible and the morisco forgeries (the Sacromonte texts) played a part in the historical and national construction of Spain and in the working out of the « Comentarios reales de los Incas ».